Retirement lifestyle conceptualization and well-being in recent retirees. Issue 11 (1st November 2020) - Bačová, Viera; Halama, Peter
ABSTRACT: The retirement literature contains four distinct conceptualizations of retirement lifestyle. Retirement can be seen as an opportunity to make a new start, the continuation of a pre-retirement lifestyle, an unwelcome imposed disruption, and a transition to old age. This research examines the conceptualizations of retirement lifestyle and how they relate to retirement adjustment and well-being in recent retirees (N = 173). A factor analysis confirmed the existence of four factors identifying four retirement conceptualizations. Although previous studies have presented retirement conceptualizations as mutually incompatible, significant relationships were found between them in this research, indicating that recent retirees can synchronously conceptualize seemingly distinct lifestyles. The cluster analysis identified three types of retirees in the sample. These types were labeled to reflect the prevailing retirement lifestyle concepts. The first type of retiree (N = 90) is "New beginning and continuation, " the second (N = 44) is "Imposed disruption without hope, " and the third is (N = 39) "Accepted disruption and ending." The analysis of variance revealed the three types differ significantly in the level of satisfaction in retirement, subjective happiness, and life meaningfulness – with the highest level being found in the first retiree type and the lowest level in the second retiree type. The findings suggest that conceptualizations of retirement lifestyle change over time and affect psychological well-being in the recent retiree cohort. The theoretical and practical implications of the results are outlined.